STUDENTS’ WRITING ABILITY IN PARAPHRASING NEWS ITEM - Aidil Syah Putra (Globish: An English-Indonesian Journal for English, Education, and Culture, 2018)
AbstractWriting is one of skills that has to be mastered by students because by writing the writers can express ideas and thought into a good written. In SMA/MA, students often get difficulties in rewriting or paraphrasing the news item that they have read by using their own words. This matter is caused of student’s lack of vocabulary, structure, relating sentence to other sentences, also that they do not understand about the elements of the paragraph that builds a text, and they do not understand a generic structure of news item text. This research took the population of the tenth grade students of MAs Daarul Hikmah Tangerang by using cluster sampling. There are 4 (nine) classes of the tenth grade. Total population is 140 students. One of the classes was the sample. After analyzing the data, the researcher got the result of the students writing ability in paraphrasing news item on the tenth grade was Fair (50.86). There is no student got excellent category, 3 students got good (8.57) category, 20 students got fair (57.14) category, and 12 students got poor (34.29) category.Key word : Writing Ability, News Item, Text